Tool support for generating model-based test cases via web. (1st January 2014) - Arantes, Alessandro Oliveira; de Santiago, Valdivino Alexandre; Vijaykumar, Nandamudi Lankalapalli; de Souza, Erica Ferreira
Testing activities play an important role in order to obtain high quality software products. These activities become more important when considering critical software, for instance, space application software. Nowadays, there is an extensive collaboration among space institutions. So, it is more than natural to expect distributed development of software and software testing activities. Therefore, a collaborative tool hosted on the internet becomes quite useful. In this respect, WEB-PerformCharts 2.0 tool discussed in this paper moves in this direction. The tool focuses on supporting a single aspect of distributed software development: the activity of generating test cases via web. Moreover, it allows model-based test case generation by means of formal methods (formal languages statecharts and FSM) which are considered state of the art in software development. WEB-PerformCharts 2.0 can be used to generate test cases for any kind of reactive systems modelled in statecharts or FSM. We present three case studies in different application domains to demonstrate the feasibility of our tool.